Proposal for sustainable use in the Ribeirão Formiga hydrographic bowl - Delfinópolis (MG) - Rodrigues, Augusto Santos; Collares, Ana Carina Zanollo Biazotti (Sociedade & Natureza, 2017)
reated in 1972, the Serra da Canastra National Park was stablished to preserve the springs of the SāoFrancisco river, and the watersheds of the Araguai and Paraná river, and also to protect the naturalresources and the biodiversity. The SCNP has not been totally regulated yet; in it’s decree of approxi-mately 210 thousand hectares, only 70 thousand has the regularized land situation. This research aimsto evaluate the watershed of the Ribeirāo Formiga, located in a part of the land that doesn’t have theregular land situation. This river supplies the population from the Babilônia district, it’s fundamental forthe agricultural activities, and it’s the receiver of the effluent generated by the population.An ambientalanalysis was done with data from the Grande Minas Project (Collares, 2013), and with data obtainedin field investigations. The cartographic products were generated with the Arcgis tool. From the dataobtained in the area of study, and the evaluation of the current situation of the watershed, proposals ofsustainable use of the land were suggested, aiming to reduce and control the anthropic impacts found inthe ambiental unity. It was concluded in this research that community participation is indispensable in order for the sustainable proposals to work, and that researches and studies should be encouraged andfinanced by public organs, ONG’s and Universities.